Valdosta Project Change, Scrapbook, August 2000 - Valdosta Project Change (Lowndes County Historical Society, 2000)
8/3- Paulk’s move defies sound judgement- no author; 8/9- Adel council meeting erupts over race: NAACP leader, Adel city manager exchange words- Tim Storey; 8/10- Sheriff should rethink his decision- no author; 8/11- Coming home: Tuskegee airman, WWII POW to be honored in native South Georgia- Dean Poling; 8/14- Hispanics left out of storm plans- Associated Press; 8/18- Justice will always prevail in the end- Floyd E. Rose, Valdosta; 8/20- Weed and Seed picnic gets the word out: Gathering used to teach public about what project offers- Peter Failor; 8/30- Hispanic population doubles- Associated Press; 8/30- Valdosta hero who deserved better- Rev. W. F. Wade, Valdosta;
Valdosta Project Change. “Valdosta Project Change Scrapbook, August 2000,” Lowndes County Historical Society. Valdosta State University Archives and Special Collections, Valdosta Project Change Scrapbook Collection, 1997-2003. 1 PDF document and scans, 11 pages. 319 MB (335,002,019 bytes).
Keywords: Clippings (Books, newspapers, etc.); Discrimination--Prevention; Lowndes County Historical Society (Valdosta, Ga.); Nonprofit organizations; Project Change; Race discrimination--Prevention; Racism; Scrapbooks; Valdosta (Ga.) -- Social conditions; Valdosta (Ga.); Valdosta Daily Times; Valdosta Project Change